Prosedur Pemungutan Pajak Barang dan Jasa Tertentu atas jasa Kesenian dan Hiburan Pada Badan Pendapatan Daerah Kabupaten Banyuwangi - Ella Juwitasari (fakultas Ilmu Sosial dan Ilmu Politik, 2025)
Local tax is a mandatory contribution to the Region owed by individuals or entities that are compelling based on the Law, with no direct reward and used for Regional purposes for the greatest prosperity of the people. One type of local tax is PBJT on Arts and Entertainment. The purpose of the Real Work Practice activities at the Banyuwangi Regency Regional Revenue Agency is to study the PBJT Collection Procedures for Arts and Entertainment services. In writing the Community Service Report, the author uses qualitative and quantitative research methods. Qualitative methods are descriptive research. the data collected is in the form of words or pictures, so it does not emphasize numbers. While the quantitative method is research based on the philosophy of positivism, used for quantitative / statistical data collection, meaning research that can be summarized with numbers. The PBJT collection procedure for Arts and Entertainment services at the Banyuwangi Regency Regional Revenue Agency begins with registration which has three procedures, namely by coming directly to the Banyuwangi district public service mall, registering online by accessing the E-PAD web page and registering with officers who come directly to record new taxpayers. PBJT reporting on arts and entertainment services using the Self Assessment System where taxpayers self report the tax payable each month online using the E-PAD application or directly come to the Banyuwangi Regency public service mall. . After the reporting process, taxpayers will carry out the process of paying taxes owed using the method of coming directly to the Bank Jatim teller to make payments and by the Virtual Account method or using QRIS.
Reuploud Repository hasyim Mei 2026 finalisasi 22 juni 2026 Rudi H
Keywords: PBJT on Arts and Entertainment services; collection procedures; banyuwangi district local revenue agency; e-pad